Konstruksi Sosial Komunitas Daerah Aliran Sungai Subayang: (Studi di Desa Tanjung Belit Kecamatan Kampar Kiri Hulu Kabupaten Kampar) - Retno Nazar Rasmida; Rina Susanti (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The River Basin (DAS) as a place of absorption and water source for living things, forms an ecosystem and a direct relationship between humans and nature. This study aims to determine the function of the Subayang River for the DAS community in Tanjung Belit Village, and to analyze the process of interpreting the river using the social construction theory of Peter L. Berger and Thomas Luckman. This study uses a descriptive qualitative approach, with data collection techniques in the form of in-depth interviews, observation, and documentation. Data analysis uses the Miles and Huberman model. The research subjects numbered eight people, consisting of six main subjects (selected purposively) and two key subjects. The results of the study show that the Subayang River has domestic functions (consumption and MCK) and non-domestic (interaction space, economic function, mobility, culture, conservation, and disposal). The process of the community interpreting the Subayang River consists of three processes, namely externalization (Knowledge) sources of community knowledge about rivers are formed through direct experience, family heritage, social interaction, norms or unwritten rules maintained by the community. Objectivation (Attitude) of Subayang River is not only seen as a water source but as a source of life, as a sacred object, river as identity and river as a place of purification. Internalization (Action) of society carries out various actions that come from the community's response to the river. The social construction process is influenced by internal factors (Personal Experience, Cognitive Awareness, Emotional) and external factors (Family, Norms/Rules, Community Culture, Environmental Conditions).